Code Switching in Malaysian Secondary ESL Classroom: A Preliminary Study from Sabah - Jumal, Noor Azaliya Binti; AlSaqqaf, Asmaa; Mohamed, Nik Zaitun Nik (International Journal of Asian Social Science, 2019)
The dearth of research investigating the use of code-switching (CS) in English as a second language (ESL) classrooms in Sabah, Malaysia, has triggered the current study to examine this phenomenon at a secondary school in Tawau, Sabah. A qualitative approach was utilized by the present research through conducting classroom observations where data were obtained from three Form-Five ESL classes. Both teachers’ and students’ CS uses were analysed utilizing Sert (2005) functions of CS adopted from the framework proposed by Mattsson and Burenhult-Mattsson (1999), Eldridge (1996) and Cole (1998). Results revealed that teachers and students in ESL classrooms in Tawau not only use CS but they also use code mixing (CM). Furthermore, data analysis also showed that CS has different functions for both teachers and students. While teachers use CS mostly for repetition function or switch, students’ use of CS is mainly for floor holding and reiteration. Further research may explore the use of CM in ESL classroom as this area of research has not been investigated adequately whether in Malaysia in general or in Sabah in particular, which would enable future studies to determine the functions of CM and examine the differences between CS and CM in ESL classroom.